Lifecycle performance measurement of public-private partnerships: a case study in China’s water sector - Bao, Fengyu; Martek, Igor; Chen, Chuan; Chan, Albert P. C.; Yu, Yao (International Journal of Strategic Property Management, 2018)
Numerous public-private partnership (PPP) infrastructure projects have been operating in China after nearly 30 years of development. Surprisingly, few lessons and experiences have been drawn from these existing cases, thereby creating an urgent demand for a comprehensive evaluation of their performance. Thus, this paper presents a timely contribution to the assessment of a representative PPP project in China’s water sector, the Chengdu No. 6 Water Plant B Project, from a lifecycle perspective. Through a triangulation method, the project is generally deemed a success providing instructive lessons on the future evolutionary development of PPPs in China despite several imperfections caused by particular historical factors. Moreover, this paper advances the performance measurement of PPPs offering empirical insights to promote the efficacy of conceptual performance measurement frameworks. The outcomes of this research are especially valuable to the current Chinese PPP community where huge opportunities and challenges simultaneously exist.